(untitled) (Minerva, 2019)
The aim of this paper is to analyse the influence of pragmatic factors on the order of the clauses of the complex sentence, to which the theme-rheme concepts of the simple sentence can be applied. By means of this analysis it becomes clear that rhematic subordinate clauses, which are placed in front, bear emphatic value, and in this case the main clause is thematic.